Brand Ambassador and Price Shape Consumer Purchasing Decisions - Muttaqien, Habibil; Hariasih , Misti (Indonesian Journal of Law and Economics Review, 2025)
General Background: The bottled drinking water (AMDK) industry in Indonesia continues to grow rapidly, supported by increased public awareness of clean and safe water consumption. Specific Background: Within this competitive market, Le Minerale strives to strengthen consumer purchase intentions through marketing variables such as brand ambassadors, product design, and price. Knowledge Gap: Previous studies have shown inconsistent results regarding the relationship between these variables and consumer purchasing decisions, necessitating further empirical validation. Aims: This study aims to analyze the roles of brand ambassadors, product design, and price in shaping consumer purchasing decisions for Le Minerale products in Sidoarjo. Results: Using a quantitative method with 100 respondents and multiple linear regression analysis, findings reveal that brand ambassadors and price significantly and positively affect purchasing decisions, while product design has no significant effect. Novelty: This study integrates consumer perception theory with marketing mix analysis in a specific local market, providing an updated empirical perspective. Implications: The results suggest that effective marketing strategies should prioritize credible brand ambassadors and affordable pricing to enhance purchase intentions in the bottled water industry. Highlights: Brand ambassadors and price significantly influence purchasing decisions. Product design shows no significant relationship with consumer choice. Marketing strategy should focus on credibility and pricing competitiveness. Keywords: Brand Ambassador, Product Design, Price, Purchasing Decision, Marketing Management